2010
DOI: 10.1158/0008-5472.can-09-3465
|View full text |Cite
|
Sign up to set email alerts
|

Colitis-Associated Cancer Is Dependent on the Interplay between the Hemostatic and Inflammatory Systems and Supported by Integrin αMβ2 Engagement of Fibrinogen

Abstract: A link between colitis and colon cancer is well established, but the mechanisms regulating inflammation in this context are not fully defined. Given substantial evidence that hemostatic system components are powerful modulators of both inflammation and tumor progression, we employed gene-targeted mice to directly test the hypothesis that the coagulation factor fibrinogen contributes to colitis-associated colon cancer in mice. This fundamental provisional matrix protein was found to be an important determinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 44 publications
3
133
1
2
Order By: Relevance
“…Fibrin-rich matrices are an important local cue for leukocyte activation, mediated via interaction with the integrin receptor ␣ M ␤ 2 . Elimination of the ␣ M ␤ 2 binding motif on fibrinogen, while retaining clotting function, significantly protects mice in the settings of inflammatory joint disease, colitis, Duchene's muscular dystrophy, and, most notably, EAE (Adams et al, 2007;Flick et al, 2007;Steinbrecher et al, 2010;Vidal et al, 2012). In this latter context, fibrin matrices appear to drive microglial/macrophage migration and local activation events, leading to demyelination and loss of motor function in EAE (Adams et al, 2007;Davalos et al, 2012;Ryu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin-rich matrices are an important local cue for leukocyte activation, mediated via interaction with the integrin receptor ␣ M ␤ 2 . Elimination of the ␣ M ␤ 2 binding motif on fibrinogen, while retaining clotting function, significantly protects mice in the settings of inflammatory joint disease, colitis, Duchene's muscular dystrophy, and, most notably, EAE (Adams et al, 2007;Flick et al, 2007;Steinbrecher et al, 2010;Vidal et al, 2012). In this latter context, fibrin matrices appear to drive microglial/macrophage migration and local activation events, leading to demyelination and loss of motor function in EAE (Adams et al, 2007;Davalos et al, 2012;Ryu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of note in this context are well controlled and elegantly executed studies of Palumbo and colleagues who demonstrated that in a mouse model were colon cancer originates on the background of inflammatory bowel disease, coagulation factors, such as fibrinogen are an essential part of the disease pathogenesis. In this setting the leukocyte binding domain of fibrinogen (Fibγ390-396A) was required for tumor formation, a finding that suggests a link between coagulation and inflammation [109]. This is also important because in this model cancer cells are not introduced externally, but are formed endogenously in mice subjected to the proinflammatory protocol of azoxymethane and dextran sodium sulfate exposure, and thereby the related processes likely induce (transform) colonic epithelium to form a full blown adenoma [25,109].…”
Section: Coagulation System As Modulator Of Tumor Initiation Progresmentioning
confidence: 98%
“…In this setting the leukocyte binding domain of fibrinogen (Fibγ390-396A) was required for tumor formation, a finding that suggests a link between coagulation and inflammation [109]. This is also important because in this model cancer cells are not introduced externally, but are formed endogenously in mice subjected to the proinflammatory protocol of azoxymethane and dextran sodium sulfate exposure, and thereby the related processes likely induce (transform) colonic epithelium to form a full blown adenoma [25,109]. It remains unclear whether the nexus of inflammatory and coagulant events is mainly a part of the supportive niche for CSCs transformed by another mechanism (mutagenesis), or whether host responses are responsible for the transformation process.…”
Section: Coagulation System As Modulator Of Tumor Initiation Progresmentioning
confidence: 99%
“…However, Fibγ 390-396A mice have defective clearance of Staphylococcus aureus (4) and are protected against autoinflammatory disorders (5)(6)(7)(8)(9). These effects are thought to stem from the lack of fibrin-driven leukocyte responses during inflammation.…”
Section: -396amentioning
confidence: 99%